EFFECT OF BIO FERTILIZER ON MATURE OIL PALM IN NORTH SUMATRA AND RIAU - -Adiwiganda, Y . Taryo; Tarigan, Balaman; Purba, Berani (Indonesian Journal of Agricultural Science, 2006)
Chemical fertilizers have routinely been applied at oil palmplantations to maintain soil fertility. Due to the increase ofchemical fertilizer prices, some efforts have been done at suchas to reduce cost and increase efficiency in chemical fertilizerapplication at oil palm plantations include the use of biofertilizer (BF). The objective of experiment was to evaluatethe effect of reducing oil palm standard dosage of chemicalfertilizers combined with BF on mature oil palm yield. Theexperiment was carried out in 2002-2003 covering an area of4367 ha at PTPN IV in North Sumatra and of 515.58 ha atPTPN V in Riau. The planting material was Dura x Pasiferavariety and planted in 1980-1995. A randomized block designwas used having three fertilizer treatments: (A) 100% chemicalfertilizer (normal dosage), (B) 75% chemical fertilizer + BF, and(C) 50% chemical fertilizer + BF. The replications at PTPN IVand V were 11 and 7, respectively. The BF was applied firstlyin May 2002. Dosage of BF was 250 g tree-1 yr-1. The BF wasgiven in pockets with four pockets per palm tree. The parametersobserved were fresh fruit bunch (FFB) weight, averageof bunch weight, and average of bunch number. Results of theexperiments showed that palm yield treated with 75% chemicalfertilizer + BF and 50% chemical fertilizer + BF were both notsignificantly different with palm yield treated with 100%chemical fertilizer. The application of 75% chemical fertilizer+ BF and 50% chemical fertilizer + BF gave benefit of Rp509,093and Rp1,231,535 ha-1 yr-1, respectively. Technically, nutrientsgiven as chemical fertilizers using combination of 75%chemical fertilizer + BF are still higher than the nutrientstransported into 26 tons palm FFB ha-1 yr-1. Fertilizer treatmentcombination of 50% chemical fertilizer + BF will technicallybe safe only for palm yield of <16 tons palm FFB ha-1yr-1, since nutrients given as fertilizer are still higher than thosetransported into the palm yield.